2017
DOI: 10.1177/0361684316689367
|View full text |Cite
|
Sign up to set email alerts
|

White Female Bystanders’ Responses to a Black Woman at Risk for Incapacitated Sexual Assault

Abstract: We investigated White female college students' responses to risk for an incapacitated sexual assault involving a Black potential victim. Participants (N ¼ 160) read about attending a party where they saw a man lead an intoxicated woman into a private bedroom. The potential victim was referred to as having either a distinctively Black name (e.g., LaToya) or a non-distinct control name (e.g., Laura). After random assignment to one of these two conditions, participants reported on their intent to intervene and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 47 publications
5
51
0
Order By: Relevance
“…For instance, Black survivors of rape are not only considered more sexually promiscuous than White women (Donovan, 2007), they are also less likely to have the experience defined as rape, are held more responsible, and others are less likely to believe the incident should be reported to authorities, compared to White survivors of rape (Foley, Evancic, Karnik, King, & Parks, 1995). A recent study found that individuals feel less willing and less obliged to intervene in a situation involving a Black woman at risk of sexual assault, compared to a situation in which her race is unspecified (Katz, Merrilees, Hoxmeier, & Motisi, 2017).…”
Section: Mechanistic Dehumanization and Objectificationmentioning
confidence: 99%
“…For instance, Black survivors of rape are not only considered more sexually promiscuous than White women (Donovan, 2007), they are also less likely to have the experience defined as rape, are held more responsible, and others are less likely to believe the incident should be reported to authorities, compared to White survivors of rape (Foley, Evancic, Karnik, King, & Parks, 1995). A recent study found that individuals feel less willing and less obliged to intervene in a situation involving a Black woman at risk of sexual assault, compared to a situation in which her race is unspecified (Katz, Merrilees, Hoxmeier, & Motisi, 2017).…”
Section: Mechanistic Dehumanization and Objectificationmentioning
confidence: 99%
“…More recently, Katz et al (2017) manipulated the name of a potential rape victim in a high-risk for sexual assault situation to appear stereotypically Black or White. They then asked White women of different levels of symbolic racism (similar to modern racism) to assign blame to the victim.…”
Section: Modern Racism and Rape Victim Blamementioning
confidence: 99%
“…Previous research suggests that racism and sexism are related (Aghasaleh, 2018;B€ ackstr€ om & Bj€ orklund, 2007;, and may even be explained by similar underlying constructs, such as the social dominance orientation, empathy, or right-wing authoritarianism (B€ ackstr€ om & Bj€ orklund, 2007), indicating that racism and sexism, as well as other types of prejudices, share fundamental properties. It could be argued that a subtle form of sexism might be rape victim blaming attitudes, which have been studied in several previous studies (e.g., Canto et al, 2018;Donovan, 2007;George & Martinez, 2002;Katz et al, 2017;Sj€ oberg & Sarwar, 2020;Str€ omwall et al, 2014). Specifically, when asked to evaluate an ambiguous rape situation, it could be hypothesized that individuals high in racism would be more prone to blame a rape victim and exculpate the perpetrator compared to individuals low in racism.…”
Section: Introductionmentioning
confidence: 98%
“…It has been found that if one person stands up, more are likely to do so, but if no one helps, people are left wondering what the right thing to do is (Fischer et al, 2011). Other barriers to bystander intervention models include: unconscious racial bias (Katz, Merrilees, Hoxmeier, & Motisi, 2017), rape myth acceptance, bystander efficacy, alcohol use/intoxication, peer perceptions, perceptions of sexual assault severity, and gender of the bystander (Labhardt, Holdsworth, Brown, & Howat, 2017), with males less likely to intervene (Leone & Parrott, 2019).…”
Section: Sexual Assault Preventionmentioning
confidence: 99%